Irigasi Presisi Berbasis IoT untuk Peningkatan Efisiensi Air dan Produktivitas Pepaya di Kendal - Mahmudi; Agus Purwanto; Wahyu Imam Santoso; Eko Riyanto (Abdi Masya, 2026)
The Melati Makmur Farmer Group in Mlatiharjo Village, Patean District, Kendal Regency, faces significant challenges in managing agriculture, particularly due to inefficient use of water and fertilizer. Manual irrigation of plants leads to resource waste and reduced crop yields. Additionally, pest attacks further decrease the quality of agricultural produce. This community service aims to introduce Internet of Things (IoT) technology to monitor soil moisture, temperature, and plant water needs in real time. With this technology, farmers can save up to 30% on water use and reduce pest damage. The methods employed include socialization, training, IoT sensor installation, and ongoing support in using the technology. The results show increased water-use efficiency, a 50% increase in crop yields, and farmers' ability to operate the technology effectively. Despite challenges related to infrastructure and farmer adaptation, the use of solar panels and intensive mentoring overcame these obstacles. In conclusion, the implementation of IoT technology has a positive impact on agricultural efficiency and can be further expanded in the agricultural sector.